What drives the acquisition behavior of agroholdings? Performance analysis of agricultural acquisition targets in Northwest Russia and Ukraine - Igor Ostapchuk; Taras Gagalyuk; David Epshtein; Abusupyan Dibirov (International Food and Agribusiness Management Review, 2021)
This article provides pioneering empirical evidence on the selection of acquisition targets by agroholdings in transition economies. We use panel data from Ukraine and Northwest Russia covering the years 2005-2016. Binomial logistic regression models were estimated to analyze the impacts of farm capital strength, financial performance and size on the farm's likelihood of being acquired by an agroholding. Our results indicate that agroholding target selection considerations tend to change over time and have shifted from farm size to farm performance in both countries. However, agroholdings in both countries prefer to `grab lemons', i.e. acquire poorly performing farms, but they differ with respect to target selection criteria. Agroholdings in Northwest Russia tend to focus on farm profitability, while their Ukrainian counterparts emphasize the capital structure of the target farms.
Keywords: G34; L25; Q14; 330; acquisition target selection; agroholdings; Northwest Russia; pre-acquisition performance; Ukraine